Formation of future doctors' research competence on the basis of their cognitive activity - Makarenko, Alexander (ScienceRise: Pedagogical Education, 2017)
Organization of cognitive activity of medical students at different levels of research work is described. It is contributed to the formation of future doctors’ research competence at various levels of research. Such work includes the following components: - search for scientific information (tasks aimed at recording and correlating information data, determination of their consistency and inconsistency, correlation of the stages of scientific research, bringing each conclusion, finding of direct and indirect links and justification of the conclusions, checking the effectiveness of the search, etc.); - Discussion of the patient problem during consultations (technologies that provide for work in groups); - writing of abstracts and articles and other scientific works as a result of their participation in the work of problem groups, scientific groups, problem student laboratories, work on projects. The effectiveness of various training technologies in the process of organizing such activities, in particular, work in small groups and the project method is actively used in the study of the disciplines of the natural-science cycle